TRANSLATION PROCEDURES OF CULTURE-SPECIFIC TERMS IN INDONESIAN POEMS IN ON FOREIGN SHORES - Paskalis Damar Aji Kurnia; Barli Bram (Masyarakat Linguistik Indonesia, 2021)
This paper aimed firstly to explore culture-specific terms identified in the anthology of poems On Foreign Shores: American Images in Indonesian Poetry and secondly to analyze translation procedures employed to translate the culture-specific terms from Indonesian into English. Data were taken from the anthology entitled On Foreign Shores and analysed using Newmark’s (1988) and Vinay and Darbelnet’s (1958) translation procedures. Results showed 23 culture-specific terms were discovered in 15 poems in the Indonesian language. Of the 23 culture-specific terms, such as daun ketapang, gayam, and kopiah, seven belong to the ecology category, three to the material culture category, nine to the social culture category, one to the organizations, ideas and customs category, and three to the gestures and habits category. Results also showed five of 15 translation procedures were employed to translate the 23 culture-specific terms found in On Foreign Shores. The five procedures were functional equivalence or equivalence, cultural equivalence or adaptation, descriptive equivalence, transference, and reduction.